2014
DOI: 10.1159/000358632
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Suppressors of Cytokine Signaling 1 Promotes the Neuronal Differentiation of C17.2 Neural Stem Cells

Abstract: Objective: To investigate the role and mechanism of suppressor of cytokine signaling 1 (SOCS1) in the regulation and differentiation of C17.2 neural stem cells (NSCs). Methods: In this study, lentiviral (LV)-SOCS1-enhanced green fluorescent protein (EGFP) was constructed and transfected into C17.2 NSCs. There were three groups of C17.2 NSCs: LV-SOCS1-EGFP, LV-EGFP, and phosphate-buffered saline (PBS). The expression levels of microtubule-associated protein 2 (MAP2), glial fibrillary acidic protein (GFAP), myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The migration distance of neural cells from the edge of the neurospheres was measured by Image-J software. Immunostaining was performed to visualize Nestin (NSCs marker) 23 and microtubule-associated protein-2 (MAP2, neuron marker) 24 as described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The migration distance of neural cells from the edge of the neurospheres was measured by Image-J software. Immunostaining was performed to visualize Nestin (NSCs marker) 23 and microtubule-associated protein-2 (MAP2, neuron marker) 24 as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Single cells were seeded at 2 × 10 5 cells/well onto a six-well PDL-coated plate and then treated with different concentrations of OA (10, 20, and 40 μM). After incubation for 7 days, NSC differentiation was detected by measuring the levels of differentiation markers, including Nestin, MAP2, and glial fibrillary acidic protein (GFAP, astrocytes marker) 24 , by western blotting and immunofluorescence staining.…”
Section: Methodsmentioning
confidence: 99%
“…During such co-regenerative process, it has also been confirmed to participate in the generation of the nerve system. In 2015, a specific study [ 108 ] on neuron stem cells confirmed that the differentiation of neurons may be regulated by such gene.…”
Section: Discussionmentioning
confidence: 99%
“…SOCSs also play important roles in neuronal differentiation and regeneration, neurogenesis, and nervous system development. SOCS1 regulates IFN-γ-mediated survival of sensory neurons [ 100 ] and NSC proliferation and differentiation into neurons [ 101 , 102 ].…”
Section: Characteristics Of Socs Proteins and Their Roles In Neuronal...mentioning
confidence: 99%